Co-hydrothermal carbonization of lignocellulosic biomass and waste polyvinyl chloride for high-quality solid fuel production: Hydrochar properties and its combustion and pyrolysis behaviors - Zhang, Xiaojuan; Zhang, Lei; Li, Aimin (Bioresource technology, 2019)
[Display omitted] •The waste PVC and pinewood sawdust were employed to produce hydrochar.•Effects of hydrothermal reaction temperature and mixing ratio were investigated.•The effects of Co-HTC on the combustion and pyrolysis behavior were evaluated.•The synergistic effect and dichlorination mechanism involved were discussed. The rigid polyvinyl chloride (PVC) and pinewood sawdust (PS) were selected for co-hydrothermal carbonization (Co-HTC) process. The effects of hydrothermal reaction temperatures and the mixing ratios of raw materials were fully investigated. The results showed that hydrothermal reaction temperature increased could significantly promote the dechlorination efficiency at the mixing ratio of 1:1, which was 92.98% at 280 °C. The experimental HHV were higher than theoretical value and increased by 4.04%, 8.21% and 2.81% at the mixing ratios of 3:1, 1:1 and 1:3. The combustion behavior and the thermodynamic parameters of hydrochar were determined, and the activation energy tended to decrease. The Py-GC/MS analysis showed the changes of the distribution for the pyrolysis product. Aliphatic and aliphatic cyclic hydrocarbons were the main products of hydrochar pyrolysis, and the yield could be promoted by Co-HTC process. According to the FTIR spectrum, elimination and substitution were the primary mechanisms of dechlorination.